Hematogenous metastasis and tumor dormancy as concepts or dogma? The continuum of vessel co-option and angiotropic extravascular migratory metastasis as an alternative - Lugassy, Claire; Kleinman, Hynda K.; Cassoux, Nathalie; Barnhill, Raymond (Frontiers in Oncology, 2022)
It has been accepted for many years that tumor cells spread via the circulation to distant sites. The latency period between treatment and tumor recurrence has been attributed to dormant cells in distant organs that emerge and grow as metastatic tumors. These processes are accepted with an incomplete demonstration of their existence. Challenging such a well-established accepted paradigm is not easy as history as shown. An alternative or co-existing mechanism involving tumor cell migration along the outside of the vessels and co-option of the blood vessel has been studied for over 25 years and is presented. Several lines of data support this new mechanism of tumor spread and metastatic growth and is termed angiotropic extravascular migratory metastasis or EVMM. This slow migration along the outside of the vessel wall may explain the latency period between treatment and metastatic tumor growth. The reader is asked to be open to this possible new concept in how tumors spread and grow and the reason for this latency period. A full understanding of how tumors spread and grow is fundamental for the targeting of new therapeutics.